2012
DOI: 10.1097/ijg.0b013e3181fc800a
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Status in Primary Angle-closure Glaucoma With a History of Acute Attack

Abstract: Corneal endothelial cell density was significantly reduced in aPACG eyes compared with normal eyes. No significant difference in endothelial cell density of aPACG eyes was noted when compared with fPACG or cPACG eyes. Corneal endothelial cell density was negatively associated with the duration of the acute attack, but was not associated with demographic and biometric characteristics. Central corneal thickness and corneal curvature radius were not associated with an earlier acute angle-closure attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 0 publications
2
30
2
1
Order By: Relevance
“…Unfortunately, we do not have data on the duration of the acute attack, but we speculate that early and rapid resolution of an acute attack reduces the risk of corneal endothelial damage in the long term. Our findings of the lack of correlation between ECD and disease duration and ocular biometric parameters corroborates the findings of Chen et al 29 in their study of acute PACG eyes. We also noted no correlation between ECD and glaucoma medications.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, we do not have data on the duration of the acute attack, but we speculate that early and rapid resolution of an acute attack reduces the risk of corneal endothelial damage in the long term. Our findings of the lack of correlation between ECD and disease duration and ocular biometric parameters corroborates the findings of Chen et al 29 in their study of acute PACG eyes. We also noted no correlation between ECD and glaucoma medications.…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that changes in structure and function of corneal endothelial cells following an acute increase in IOP is transient and revert to pre-elevated IOP level once the acute crisis resolves. A study by Chen et al 29 found no significant differences in ECD of acute PACG eyes when compared with fellow PACG or chronic PACG eyes, while there was significantly lower ECD when compared with normal. Interestingly, a recent study on a rat model showed that an acute increase in IOP resulted in structural and functional damage of corneal endothelial cells, which gradually reversed when the acute rise in IOP resolved.…”
Section: Discussionmentioning
confidence: 91%
“…; Chen et al. ). This loss was primarily affected by age and mean duration of attack (Malaise‐Stals et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Chen et al. ). Laser interventions after acute attacks may therefore impose a higher risk of further endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…The more dense the lens and the more shallow the anterior chamber, the higher the risk of the corneal endothelium being jeopardized from the prior acute angle closure. 21 Waiting for the development of elevated IOP would also contribute to the complexity of the cataract extraction. Laser gonioplasty would have been technically challenging due to unfavorable iris curvature.…”
Section: Discussionmentioning
confidence: 99%